2006
DOI: 10.1007/s00484-006-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenological models for blooming of apple in a mountainous region

Abstract: Six phenological series were available for 'Golden Delicious' apple blooming at six sites in Trentino, an alpine fruit-growing region. Several models were tested to predict flowering dates, all involving a "chilling and forcing" approach. In many cases, application of the models to different climatic conditions results in low accuracy of prediction of flowering date. The aim of this work is to develop a model with more general validity, starting from the six available series, and to test it against five other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 43 publications
2
33
0
1
Order By: Relevance
“…Parallel models do not explain how chill accumulation can compensate for heat during bud development, but they introduce the concept that a higher accumulation of chilling during the winter results in a lower heat requirement during the forcing stage. This approach, implemented also in the "Modified Utah" model, was considered suitable by Rea and Eccel (2006), and is used in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel models do not explain how chill accumulation can compensate for heat during bud development, but they introduce the concept that a higher accumulation of chilling during the winter results in a lower heat requirement during the forcing stage. This approach, implemented also in the "Modified Utah" model, was considered suitable by Rea and Eccel (2006), and is used in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Trees and shrubs that require winter chill rely on the occurrence of cold conditions during the winter, in order to break their dormancy and initiate fructification. In spite of the importance of this phenomenon for horticultural production, the physiological details of this process are still relatively unknown, and the existence of several competing models to quantify winter chill suggests that the climatic conditions required to break a tree's dormancy are as yet relatively poorly understood and possibly vary between species (Kozlowski and Pallardy 2002;Rea and Eccel 2006). This is also reflected by the fairly elaborate structure of some existing models and by their specificity to a certain species or even variety (Richardson et al 1974;Shaltout and Unrath 1983).…”
Section: Introductionmentioning
confidence: 99%
“…= 5.7-0.3(T aN ); r 2 = 1.00). other authors (Rea & eccel 2006) have also found that long-term mean temperatures are useful for constructing specific site-dependent variables.…”
Section: Model Parametersmentioning
confidence: 97%
“…latitude may be an effective parameter because the three research orchards used are located at similar altitudes, and so latitude may be acting as a surrogate measure of mean annual temperature. If orchards at greater range of altitudes are compared (Rea & eccel 2006) then latitude alone may not adequately characterise the sites. The similarity of the location-dependent models implies that the site factors are closely linked to some aspect of climate, and regression analysis reveals that, for the three sites used, the site offset and the long-term mean annual temperature are linearly correlated (site offset Table 4 Coefficients of determination (r 2 ) for regressions of flower production (Flowers WB ) against individual mean monthly temperatures and hydrogen cyanamide usage, using flowering and temperature data for research orchards 1996-98 (n = 18).…”
Section: Model Parametersmentioning
confidence: 99%